Extending pathways and processes using molecular interaction networks to analyse cancer genome data - Glaab, Enrico; Baudot, Anaïs; Krasnogor, Natalio; Valencia, Alfonso (BioMed Central Ltd, 2010)
BACKGROUND: Cellular processes and pathways, whose deregulation may contribute to the development of cancers, are often represented as cascades of proteins transmitting a signal from the cell surface to the nucleus. However, recent functional genomic experiments have identified thousands of interactions for the signalling canonical proteins, challenging the traditional view of pathways as independent functional entities. Combining information from pathway databases and interaction networks obtained from functional genomic experiments is therefore a promising strategy to obtain more robust pathway and process representations, facilitating the study of cancer-related pathways.